(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Research background and hypothesis. The society is concerned not only about worsening student health, but also medically unexplainable psychosomatic complaints which can be the risk factor for various health and behavioural problems (WHO, 2006). Research aim was to determine the dependence of psychosomatic complaints experienced by 10–15-year-old students on their physical activity, age and gender. Research methods. With reference to the international questionnaire of student health and lifestyle (WHO, 2006), a questionnaire containing 31 questions was constructed for the research. Its answers about physical activity were coded from 1 – never to 5, 7, 8 – different variants of often. The questionnaire survey was conducted in February, 2012, in two schools of Kaunas city. The research participants were 293 V–VIII-grade 10–15-year-old students. The answers were analysed with reference to students’ physical activity, age and gender. Research results. Most respondents were moderately or intensively physically active: more of them were younger (10–12 years) than older (13–15 years), and there were more boys than girls. The students often exercised and did sports individually. Health self-assessment as good or even perfect was demonstrated by most physically active students. During the last 6 months they more rarely felt various psychosomatic complaints, especially related to negative emotions. Students of low physical activity felt more various psychosomatic complaints. Conclusion. Physically more active students rarely experienced psychosomatic complaints, which show that physical activity is a significant factor reducing negative psychosomatic emotions. Keywords: schoolchildren’s physical activity, health self-assessment, psychosomatic complaints.